2020
DOI: 10.1590/0001-3765202020200834
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic abnormalities in COVID-19: A guided review

Abstract: The spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has already taken on pandemic proportions, affecting over 213 countries in a matter of weeks. In this context, several studies correlating hemostatic disorders with the infection dynamics of the new coronavirus have emerged. These studies have shown that a portion of the patients affected by Coronavirus Disease 2019 (COVID-19) have prolonged prothrombin time (PT) and activated partial thromboplastin time (APTT), elevated D-dimer levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 89 publications
0
18
0
1
Order By: Relevance
“…[35][36][37] Studies have elucidated that acute respiratory distress syndrome and coagulation dysfunction are related to the renin-angiotensin-aldosterone system and blood coagulation pathways, which are altered by SARS-CoV-2 host cell invasion via ACE2. [38][39][40] Clinical and nonclinical studies revealed an association between these comorbidities, while SARS-CoV-2 infection decreases ACE2 expression, ACE2 deficiency is reported to cause cardiac overload and kidney inflammation. [40][41][42][43] Elevated blood glucose is also associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Studies have elucidated that acute respiratory distress syndrome and coagulation dysfunction are related to the renin-angiotensin-aldosterone system and blood coagulation pathways, which are altered by SARS-CoV-2 host cell invasion via ACE2. [38][39][40] Clinical and nonclinical studies revealed an association between these comorbidities, while SARS-CoV-2 infection decreases ACE2 expression, ACE2 deficiency is reported to cause cardiac overload and kidney inflammation. [40][41][42][43] Elevated blood glucose is also associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…When expressed, TF serves as a receptor for factor VIIa, and the binding of factor VIIa to TF initiates the coagulation cascade. This leads to thrombin generation and sequential clot formation with the deposition of fibrin protofibrils (Hergenhahn et al, 2002;Butenas et al, 2008;D'Alessandro et al, 2018;Sathler, 2020).…”
Section: Curcumin In Hemostatic Disordersmentioning
confidence: 99%
“…Other studies have also reported chronic liver disease and renal disease as risk factors [36][37][38] . Studies have elucidated that acute respiratory distress syndrome and coagulation dysfunction are related to the renin-angiotensin-aldosterone system and blood coagulation pathways, which are altered by SARS-CoV-2 host cell invasion via ACE2 [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%